Vascular insult in neonatal retinal hemorrhage: computational analysis of a fundus-segmented blood vessel network - Matthew R. Lam; Jose A. Colmenarez; Pengfei Dong; Linxia Gu; Donny W. Suh (Scientific Reports)
Abstract Common hypotheses for the biomechanical cause underlying neonatal retinal hemorrhage include elevated intracranial pressure (ICP) inducing venous outflow obstruction and retinal deformation. A finite element computational model of the eye, optic nerve, and orbit was simulated with particular attention to the retinal vessels to analyze stress and strain on these structures during external head compression associated with normal vaginal delivery. Pressure from maternal contractions displaced the eye backward into the orbit, and the stiff optic nerve sheath provided localized resistance to this posterior displacement at its insertion point, resulting in tensile strain of 2.5% in the peripapillary (central) retina. Correspondingly, retinal vessels experienced tensile stress of up to 2.3 kPa near the optic nerve insertion point and opposing compressive stress of up to 3.2 kPa further away. The optic nerve was longitudinally compressed and experienced a mean radial tensile strain of 2.0%. Overall, forces associated with maternal labor resulted in a pattern of eye deformation that stretched the central retina in this simulation, mirroring the classical posterior localization of neonatal retinal hemorrhage. The optic nerve increased modestly in diameter despite rising ICP, suggesting retinal deformation is a more likely mechanism for retinal hemorrhage than occlusion of the central retinal vein.